Age-related changes of vitamin C levels in aqueous humour - Čanadanović, Vladimir; Latinović, Slobodanka; Barišić, Sava; Babić, Nikola; Jovanović, Sandra (Vojnosanitetski pregled, 2015)
Background/Aim. Age-related cataract is a common disease among senior population. Vitamin C is the most effective reducing hydrosoluble antioxidant causing reduction in the levels of free radicals in crystaline lens. The aim of this study was to evaluate the age-related change of vitamin C (L-ascorbic acid) level in the aqueous humor of patients with senile cataract. Methods. This prospective study included 74 patients, divided into 3 age groups, with age-related cataract, underwent routine phaco cataract surgery with intraocular lens implantation. Aqueous humor was aspirated from 74 eyes at the beginning of phacoemulsification. The levels of vitamin C (L-ascorbic acid) in aqueous humor were determined with high-performance liquid chromatography (HPLC). Results. The average age of patients included in the study was 65 ± 9.85 years (54–87 years). The level of vitamin C in aqueous humor was 152.78 ± 7.0125 µg/mL in the group A (50–59 years), 134.15 ± 5.1569 µg/mL in the group B (60–69 years) and 106.51 ± 5.44 µg/mL in the group C (over 70 years). Conclusion. The amount of vitamin C in aqueous humor of patients with age-related cataract is decreasing with age. There was a statistically significant change (p < 0.001) of vitamin C aqueous concentration in the patients of different age. This decrease could play a role in susceptibility to cataract formation in older population.